2019
DOI: 10.3389/fneur.2019.00516
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Channelopathies at Neuromuscular Junction

Abstract: The neuromuscular junction, also called myoneural junction, is a site of chemical communication between a nerve fiber and a muscle cell. There are many types of channels at neuromuscular junction that play indispensable roles in neuromuscular signal transmission, such as voltage-gated calcium channels and voltage-gated potassium channels on presynaptic membrane, and acetylcholine receptors on post-synaptic membrane. Over the last two decades, our understanding of the role that autoantibodies play in neuromuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 195 publications
(225 reference statements)
0
23
0
1
Order By: Relevance
“…Electromyography (EMG) revealed myopathic changes in three patients (3/4) and neurogenic changes in all the patients (4/4). All patients (4/4) showed decreased or absent sensory nerve conduction velocity and decreased amplitude, suggesting sensory nerve impairment with axonal degeneration 9 . Specifically, one patient (1/4) showed decreased motor nerve conduction velocity, suggesting that the motor nerve was also impaired.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Electromyography (EMG) revealed myopathic changes in three patients (3/4) and neurogenic changes in all the patients (4/4). All patients (4/4) showed decreased or absent sensory nerve conduction velocity and decreased amplitude, suggesting sensory nerve impairment with axonal degeneration 9 . Specifically, one patient (1/4) showed decreased motor nerve conduction velocity, suggesting that the motor nerve was also impaired.…”
Section: Resultsmentioning
confidence: 96%
“…All patients (4/4) showed decreased or absent sensory nerve conduction velocity and decreased amplitude, suggesting sensory nerve impairment with axonal degeneration. 9 Specifically, one patient (1/4) showed decreased motor nerve conduction velocity, suggesting that the motor nerve was also impaired. Further details of the demographic, clinical statistics, and EMG of the cohort are listed in Tables 1 and 2 and in Table S1 in the Appendix S1.…”
Section: Demographic and Clinical Featuresmentioning
confidence: 98%
“…Generally, the onset occurs in the neonatal period. The diagnosis of congenital myopathy should be based on a careful review of the clinical features and confirmed by additional investigations, with an exclusionary diagnosis of other myopathies (2,3). Previously, histopathologically oriented classification was widely used for the diagnosis of congenital myopathy, which, although still in use, tends to be replaced by genetic diagnosis in the golden era of modern genetics (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the related autoimmune NMJ disorders such as MG and Lambert-Eaton syndrome, CMS with CHRNE mutations is not caused by an immune response, so theoretically, immunosuppressors are not effective [ 61 , 62 ]. Most pharmacological strategies for CMS with CHRNE mutations widely depend upon whether it is beneficial to upregulate the amount of available ACh in the synaptic cleft (such as AChEIs and DAP) or to shorten the excessive duration of synaptic current by reducing the channel-open time (such as FLX and QUIN).…”
Section: Discussionmentioning
confidence: 99%